Trichoderma-Enhanced Compost: A Dual Strategy for Southern Blight Disease Suppression and Tomato Yield Improvement - Md. Abdus Salam; Md. Khurshed Alam Bhuiyan; Md. Ismail Hossain Mia; Md. Abu Ashraf Khan; M. Mofazzal Hossain; Md. Tanbir Rubayet (Journal of Agriculture and Applied Biology, 2026)
Southern blight, caused by Sclerotium rolfsii (Sr), is a major constraint to tomato production. We isolated 20 Sr strains and identified Sr-4 as the most virulent based on pathogenicity assays. In parallel, 102 Trichoderma harzianum (Th) isolates were screened, with four inhibiting Sr growth by ≥75% in dual culture; PABT-22 showed the highest inhibition. Pot and field experiments evaluated Trichoderma-fortified compost (TFC; 2.0–4.0 × 10⁸ spores mL⁻¹). TFC applied at 3.0 × 10⁸ spores mL⁻¹ (T7) reduced disease incidence to 8.4% and percent disease index (PDI) to 5.2%, providing 71.4% control compared with the pathogen control. T7 also achieved the highest yield (64.43 t ha⁻¹; +59.1%) and enhanced fruit quality, including increased β-carotene and lycopene content. These findings demonstrate that TFC, particularly PABT-22 at 3.0 × 10⁸ spores mL⁻¹, offers an effective, residue-free strategy for suppressing southern blight while improving yield and nutritional quality in tomato.